The influence of a dentin desensitizer on the microtensile bond strength of two bonding systems - Seara, S. F.; Erthal, B. S.; Ribeiro, M.; Kroll, L. [UNESP]; Pereira, G. D.S. (My University, 2002)
A laboratory study evaluated the influence of a dentin desensitizer (D/Sense 2) on the microtensile bond strength of two adhesive systems: a self-etching primer (Bistite II SC) and a one-bottle adhesive (Prime & Bond 2.1). Sixteen crown dentin discs were obtained from extracted sound human third molars. Dentin surfaces were ground with 600 grit silicon carbide (SiC) abrasive papers to produce a standardized smear layer. Teeth were randomly divided into four groups (n=4). G1-D/Sense 2 + Prime & Bond 2.1; G2-D/Sense 2 + Bistite II SC; G3- and G4-dentin surfaces were bonded with Prime & Bond 2.1 and Bistite II SC, respectively, with no previous treatment with D/Sense 2. Eight mm high resin composite crowns (TPH Spectrum) were incrementally built-up on the treated surfaces. One sample from each group was prepared for evaluation of the hybrid layer on SEM. The specimens for the microtensile test were serially sectioned perpendicular to the adhesive layer to obtain 1 mm2 bounded sticks. Then, each stick was submitted to the microtensile test performed at a 0.5 mm/min crosshead speed. One-way ANOVA and Tukey test showed statistically significant differences among the groups (p<0.05). Values in MPa were: G1-17.85; G2-9.88; G3-35.16; G4-15.57. Based on the results of this study, it can be concluded that the D/Sense 2 desensitizer decreased the bond strength of Prime & Bond 2.1 and Bistite II SC bonding systems. © Operative Dentistry, 2002.